2007
DOI: 10.1007/s00439-007-0330-6
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of longevity phenotype in mtDNA haplogroups D4b2b, D4a, and D5 in the Japanese population

Abstract: We report new results from the re-analysis of 672 complete mitochondrial (mtDNA) genomes of unrelated Japanese individuals stratified into seven equal sized groups by the phenotypes: diabetic patients, diabetic patients with severe angiopathy, healthy non-obese young males, obese young males, patients with Alzheimer's disease, patients with Parkinson's disease and centenarians. Each phenotype had 96 samples over 27 known haplogroups: A, B4a, B4b, B4c, B*, B5, D*, F1, F2, M*, M7a, M7b, M8, M9, D4a, D4b1, D4b2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 21 publications
0
72
1
1
Order By: Relevance
“…The frequency of the Mt5178A genotype, a genetic marker of mitochondrial haplogroup D, is significantly higher in Japanese centenarians than in the general population (Alexe et al 2007;Tanaka et al 1998) and it is reported that individuals with Mt5178A (mitochondrial haplogroup D) are less susceptible to lifestyle-related adult-onset diseases, for example hypertension (Kokaze et al 2007), diabetes (Wang et al 2001), metabolic syndrome ), myocardial infarction (Mukae et al 2003;Takagi et al 2004), and cerebrovascular diseases (Ohkubo et al 2002), than those with Mt5178C. Mt5178 C/A polymorphism is, moreover, also reported to be associated with blood pressure (Kokaze et al 2004a(Kokaze et al , 2007, serum lipid levels (Kokaze et al 2001(Kokaze et al , 2003a, fasting plasma glucose levels and glucose tolerance (Kokaze et al 2005a), serum uric acid levels (Kokaze et al 2006), intraocular pressure (Kokaze et al 2004b), hematological data (Kokaze et al 2005b), and serum protein fraction levels (Kokaze et al 2002(Kokaze et al , 2003b, and its interaction with smoking habits is associated with serum triglyceride levels (Kokaze et al 2003a), intraocular pressure (Kokaze et al 2004b), red blood cell counts (Kokaze et al 2005b), and serum protein fraction levels (Kokaze et al 2003b).…”
Section: Introductionmentioning
confidence: 93%
“…The frequency of the Mt5178A genotype, a genetic marker of mitochondrial haplogroup D, is significantly higher in Japanese centenarians than in the general population (Alexe et al 2007;Tanaka et al 1998) and it is reported that individuals with Mt5178A (mitochondrial haplogroup D) are less susceptible to lifestyle-related adult-onset diseases, for example hypertension (Kokaze et al 2007), diabetes (Wang et al 2001), metabolic syndrome ), myocardial infarction (Mukae et al 2003;Takagi et al 2004), and cerebrovascular diseases (Ohkubo et al 2002), than those with Mt5178C. Mt5178 C/A polymorphism is, moreover, also reported to be associated with blood pressure (Kokaze et al 2004a(Kokaze et al , 2007, serum lipid levels (Kokaze et al 2001(Kokaze et al , 2003a, fasting plasma glucose levels and glucose tolerance (Kokaze et al 2005a), serum uric acid levels (Kokaze et al 2006), intraocular pressure (Kokaze et al 2004b), hematological data (Kokaze et al 2005b), and serum protein fraction levels (Kokaze et al 2002(Kokaze et al , 2003b, and its interaction with smoking habits is associated with serum triglyceride levels (Kokaze et al 2003a), intraocular pressure (Kokaze et al 2004b), red blood cell counts (Kokaze et al 2005b), and serum protein fraction levels (Kokaze et al 2003b).…”
Section: Introductionmentioning
confidence: 93%
“…reporting no association between mtDNA haplogroups and EL (Pinos et al ., 2012) but Dominguez‐Garrido and co‐workers finding that the Caucasian haplogroup J (which would be associated with lower mtDNA damage) might confer a higher chance to attain high longevity (85+years) compared with other haplogroups in Northern Spaniards (DomĂ­nguez‐Garrido et al ., 2009). On the other hand, although mtDNA haplogroups D4b2b, D4a, and D5 are not associated with type 2 diabetes (Fuku et al ., 2007), they are linked with EL in Japanese population (Alexe et al ., 2007; Bilal et al ., 2008). We also showed that the mtDNA m.1382A>C polymorphism, which is specific for the ancestor haplogroup D4b2, is associated with EL in the Japanese population (Alexe et al ., 2007).…”
Section: Mitochondrial Haplogroups and Elmentioning
confidence: 99%
“…On the other hand, although mtDNA haplogroups D4b2b, D4a, and D5 are not associated with type 2 diabetes (Fuku et al ., 2007), they are linked with EL in Japanese population (Alexe et al ., 2007; Bilal et al ., 2008). We also showed that the mtDNA m.1382A>C polymorphism, which is specific for the ancestor haplogroup D4b2, is associated with EL in the Japanese population (Alexe et al ., 2007). …”
Section: Mitochondrial Haplogroups and Elmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported significant associations between specific mitochondrial haplogroups and myocardial infarction 6) , atherosclerotic cerebral infarction 7) , metabolic syndrome 8) and longevity among the Japanese 9,10) , and type 2 diabetes among both Japanese and the Koreans 11) . A recent study also indicated significant associations between haplogroup T and coronary artery disease and diabetic retinopathy in Middle European Caucasians 12) .…”
Section: Introductionmentioning
confidence: 99%